PERBANDINGAN HASIL PEMERIKSAAN LED METODE WESTERGREN ANTARA SAMPEL DENGAN PENGENCERAN DAN SAMPEL TANPA PENGENCERAN - Ditaellyana Artha; Andi Auliyah Warsyidah; Melly Fitriani (Jurnal Media Laboran, 2019)
This research is motivated by the existence of laboratories that conduct examinations on EDTA blood samples without dilution. The sample taken is the blood of patients who carry out routine examinations in the laboratory of RSUD Syekh Yusuf, Gowa Regency. The purpose of this study is to find out whether there are results of the Westergren method of sedimentary blood examination (LED) for samples with dilution and samples without dilution. This type of research uses laboratory experiments with accidental sampling techniques. The results were processed through a computer using the SPSS program version 22 statistical test methods Paired Sample t Test where t-count (-6.554)> t-table (2.025) and a probability value of 0.000 <0.05 which means Ho is rejected. The conclusion of this study was obtained from the results of the study obtained in the examination of the blood sediment rate (LED) of the Westergren method between the sample with dilution and the sample without dilution (Ho rejected) so that for the LED examination the Westergren method of the sample used is EDTA blood, it is necessary to dilute the sample first.